Formation of Microdroplet in T-junction Microfluidic System: Experiment and Simulation - Thai, Nguyen Thi; Xuan, Chu Thi; Thanh, Pham Duc; Tuan, Mai Anh; Nhung, Nguyen Phuong (Communications in Physics, 2018)
The purpose of this study is to investigate the formation of the water droplet in oil using T-junction microfluidic device. Both numerical and experimental methods have been developed to explore the dependence of droplet size on the flow rate of two immiscible liquids as well as the system geometry. The velocity of droplet in channel is also considered. The microfluidic system was fabricated with lithography technique. The 3D simulation was performed based on COMSOL software using level set method. The size of droplet is inversely proportional to the flow rate of continuous phase according to exponential function, increases linearly with the flow rate of dispersed phase, and decreases as the width of lateral channel decreases.  While the decreasing of the width of the lateral channel gives rise to the increasing of droplet velocity, the velocity of droplet depends linearly on the flow rate of disperse phase. A good consistence was observed between the theory and the experiment.